Spray-dried probiotic microcapsules with calcium cross-linked oxidized starch and inulin - Mehdi Ahmadi; Fatemeh Khajeh; Sahand Sohrabi; Ramin Shahbahrami; Leila Mirmoghtadaie; Farzaneh Shahraz; Fereshte Bahmanyar; Fataneh Hashempour-Baltork; Seyede Marzieh Hosseini (Carbohydrate Polymer Technologies and Applications)
Lactobacillus acidophilus LA-5, a beneficial live microorganism requiring a minimum intake of 106 CFU for effective intestinal colonization, often suffers from poor stability in the harsh environment of gastrointestinal tract. This study explored the feasibility of using oxidized starch-inulin as a carrier material to enhance L. acidophilus LA-5 delivery and viability. The results demonstrated that Encapsulation with 1 % CaHPO4 (dicalcium phosphate) and 5 % inulin yielded the highest encapsulation efficiency (EE%) and yield (EY%). Inulin significantly enhanced probiotic survival in both SFG and, more importantly, in SIF probably through its providing nourishment for the probiotics and its potential protective effects against harsh stresses. An optimal concentration of 1 % CaHPO4 in combination with inulin was essential for achieving better protection of the encapsulated bacteria, both in SFG and SIF (gastrointestinal conditions) environments. The addition of inulin modified the low-temperature endothermic point and enthalpy ranged from -146.4 J/g to -170.6 J/g, with higher values compared to samples without inulin. The thermal behavior of the microcapsules was also slightly influenced by the different concentrations of CaHPO4. The B2 microcapsules (1 % CaHPO4, 5 % oxidized starch, 5 % inulin) demonstrated the best probiotic survivability in long-term storage stability at all temperatures and the combination of inulin and CaHPO4 provided synergistic protective effect against storage time and temperature. These findings indicate the promising application of oxidized starch-inulin and optimized CaHPO4/inulin combinations for enhancing probiotic delivery and efficacy.